Access to indole-fused benzannulated medium-sized rings through a gold(I)-catalyzed cascade cyclization of azido-alkynes - Greiner, Luca C.; Inuki, Shinsuke; Arichi, Norihito; Oishi, Shinya; Suzuki, Rikito; Iwai, Tomohiro; Sawamura, Masaya; Hashmi, A. Stephen K.; Ohno, Hiroaki (Chemistry - a European journal, 2021)
Because benzannulated and indole-fused medium-sized rings are found in many bioactive compounds, combining these fragments might lead to unexplored areas of biologically relevant and uncovered chemical space. Herein is shown that α-imino gold carbene chemistry can play an important role in solving the difficulty in the formation of medium-sized rings. Namely, phenylene-tethered azido-alkynes undergo arylative cyclization through the formation of a gold carbene intermediate to afford benzannulated indole-fused medium-sized tetracycles. The reactions allow a range of different aryl substitution patterns and efficient access to these otherwise difficult-to-obtain medium-sized rings. This study also demonstrates the feasibility of the semihollow-shaped C-dtbm ligand for the construction of a nine-membered ring.